Second Enoch: a Samaritan apocalypse - Olson, Daniel C. (Studia judaeoslavica, 2025)
"This study marks a bold new departure in 2 Enoch studies. The book has long been regarded as one of the most baffling apocalypses to come down to us from antiquity. The present work argues that 2 Enoch was written by a 1st c. CE Samaritan author whose purpose was to incorporate the Enochic tradition into Samaritanism. By identifying Enoch as the "prophet like Moses" (Deut. 18:15, 18), both during his earthly past and in the eschatological future, the author of 2 Enoch hoped to combat the Dosithean heresy and also to persuade co-religionists to resume a full sacrificial cultus in the shadow of Mt. Gerizim"--